UTILIZATION OF SPENT BLEACHING EARTH WASTE IN SOIL-CEMENT STABILIZATION FOR ROAD FOUNDATION LAYERS IN TERMS OF THE MECHANICAL PROPERTIES OF SOIL - Septianto, Septianto; Rustamaji, R.M; Priadi, Eka (Jurnal Teknik Sipil, 2023)
Various studies have been carried out to improve the parameters of soil mechanical properties. Efforts to improve the mechanical properties of the soil can be carried out in multiple ways, including automated means through compaction and chemical means through the addition of cement base materials. To improve the stability and properties of the subgrade soil, the cement base material that is commonly used is Portland Composite Cement (PCC). In several studies, apart from cement base materials, waste base materials have also been used for stabilization subgrade. This includes using bleached soil residues and rice husk ash as additives to stabilize the soil. The results showed that the use of soil bleaching waste in soil cement stabilization can be used to improve the mechanical properties of the embankment soil and the composition of the soil bleaching waste mixture so that mechanically, it is proven to provide the most effective improvement so that it can be used for road foundation layers made of cement soil. As part of this research, many tests can be carried out on normal and stabilized soils. Various percentages of SBE are 5%, 10%, 15%, 20%. PCC is introduced into the soil at a rate of 8% of the dry weight of the soil.